INTERPROFESSIONAL COLLABORATION SKILLS TRAINING FOR SOCIAL AND EDUCATION FIELDS - A MODULE PROPOSAL - Mirela ALEXANDRU (National Centre for Policy and Evaluation in Education, 2018)
The need for interprofessional collaboration may be condensed in Reid Hoffman's words "No matter how brilliant your mind or strategy is, if you're playing a solo game, you'll always lose out to a team". In the current social context, there is a strong need for the development of interprofessional collaboration skills, given the increasingly complex problems for which employees need to find solutions. Important steps have been taken at world level to develop interprofessional skills to meet demands by setting up interprofessional work organizations and implementing skills development programs in this direction. Medicines and IT domains are the most advanced in facilitating interprofessional skills development contexts, while the educational and social domains are still in their infancy, being more advanced in some countries. In Romania the interprofessional education is still pioneering, in order to support the process of its development in our country, in this article we propose an interprofessional skills training model for educational and social fields tailored to the training practice at VIA University College, Holstebro, Denmark.